Četrti mednarodni leksikografski kolokvij: Slovar in prevajanje - Vrbinc, Alenka (Mostovi (Ljubljana), 2006)
This contribution is a short report from the 4th International Lexicographic Colloquium with the title Dictionary and Translation, which took place in Maribor in October 2006. The participants, who came from Slovenia and abroad, were experts in lexicography and translation. In their papers, they covered different topics and talked about various problems connected with this field.
Keywords: leksikografija; mednarodni kolokviji